Few‐layer Bismuthene: Sonochemical Exfoliation, Nonlinear Optics and Applications for Ultrafast Photonics with Enhanced Stability. Issue 1 (26th September 2017) - Lu, Lu; Liang, Zhiming; Wu, Leiming; Chen, YunXiang; Song, Yufeng; Dhanabalan, Sathish Chander; Ponraj, Joice Sophia; Dong, Biqin; Xiang, Yuanjiang; Xing, Feng; Fan, Dianyuan; Zhang, Han
Abstract: As the last element in Group VA, bismuthene has garnered substantial interest for its unique electronic and mechanical properties and its enhanced stability. However, the mechanism that drives the light‐bismuthene interaction remains completely unclear. Herein, a sonochemical exfoliation approach is employed to deliver a successful synthesis of few‐layer bismuthene. The corresponding nonlinear optical response at the visible wavelength is investigated. The nonlinear refractive index is ∼10 −6 cm 2 /W and was measured by spatial self‐phase modulation. Thanks to its direct energy band‐gap at 1550 nm, the saturable absorption property of bismuthene is experimentally illustrated at the telecommunication band with an optical modulation depth of ∼2.03% and a saturable intensity of ∼30 MW/cm 2 . The optimization of the laser parameters resulted in the generation of an ∼652‐femtosecond optical pulse centered at 1559.18 nm. This result indicates that the bismuthene‐based saturable absorber is indeed a new and excellent material for an ultrafast saturable absorber device. Our work highlights the promise of this material in ultrafast photonics and may be considered as an important step towards bismuthene‐based photonics devices (optical modulator, optical switcher, detector, etc.). Abstract : Bismuth is the last element of group VA. Based on sonochemical approaches, few‐layer bismuthene is synthesized and the nonlinear optical properties are investigated by spatial self‐phase modulation measurement (SSPM). SSPM plays a pivotal role in the change of the nonlinear refractive index with ≈10 −6 cm 2 W −1 . The optimization of the laser parameters resulted in the generation of an optical pulse with ≈652 fs centered at the 1559.18 nm wavelength.